Implementasi Bermain Peran Makro dalam Meningkatkan Self Confidence pada Usia Prasekolah - Marita, Riza; Maryanti, Suni (BOCAH: Borneo Early Childhood Education and Humanity Journal, 2025)
Self-confidence needs to be stimulated from an early age, just before children enter elementary school. This is important because self-confidence is fundamental for children's future education. This study aims to obtain information regarding the importance of fostering self-confidence in children. Several steps in role-playing were implemented in this study, including determining the theme, telling the story to the children, determining the children's roles according to the characters, giving children time to understand each character's character, determining costumes for the actors being played, and teachers providing guidance and advice to the children on using polite and easy-to-understand sentences. This study used a descriptive qualitative method. For data analysis, Miles and Huberman were used, with 17 children aged 5-6 years as subjects. The results showed that children's self-confidence had increased significantly after the intervention. During the study, the subjects had not yet fully achieved the self-confidence aspect. However, after role-playing activities with a work theme, the children slowly began to develop their self-confidence. Therefore, it is concluded that children's self-confidence can be stimulated through various things and factors, one of which is using role-playing activities. The findings of this research are important for children and especially for teachers in developing educational programs and their implementation in children that can increase children's self-confidence increased.